Blending Through-Space and Through-Bond π-π-Coupling in [2,2']-Paracyclophane-oligophenylenevinylene Molecular Wires - Wielopolski, Mateusz; Molina-Ontoria, Agustin; Schubert, Christina; Margraf, Johannes; Krokos, Evangelos; Kirschner, Johannes; Gouloumis, Andreas; Clark, Timothy; Guldi, Dirk Michael; Martin, Nazario (Journal of the American Chemical Society, 2013)
A series of ZnP-pCp-oPPV-C60 conjugates covalently connected through [2,2′]-paracyclophane-oligophenylenevinylene (pCp-oPPV) bridges containing one, two, and three [2,2′]-paracyclophanes (pCps) has been prepared in multistep synthetic procedures involving Horner–Wadsworth–Emmons olefination reactions and/or Heck type Pd-catalyzed reactions. Molecular modeling suggests that charge transfer is effectively mediated by the pCp-oPPVs through a predominant hole-transfer mechanism. Photophysical investigation supports molecular modeling and reveals two major trends. On one hand, C60 excitation of 1, 2, and 3 leads exclusively to charge transfer between pCp and C60 to afford a ZnP-(pCp-oPPV)•+-C60•– radical ion pair state without giving rise to a subsequent charge shift to yield the ZnP•+-pCp-oPPV-C60•– radical ion pair state. On the other hand, ZnP excitation of 1, 2, and 3 results in a rather slow charge transfer between ZnP and C60, after which the ZnP•+-pCp-oPPV-C60•– radical ion pair state evolves. In temperature-dependent ZnP fluorescence experiments, which were performed in the temperature range from 273 to 338 K, two domains are discernible: low and high temperature behaviors. In the low temperature range (i.e., below 30 °C) the rate constants do not change, suggesting that a superexchange mechanism is the modus operandi. In the high temperature range (i.e., >30 °C) the rate constants increase. Moreover, we find rather strong distance dependence for 1 and 2 and weak distance dependence for 2 and 3. A damping factor of 0.145 Å–1 is derived for the former pair and 0.012 Å–1 for the latter.
EAM Import::2019-03-13